If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 12x + -9 Reorder the terms: 3x = -9 + 12x Solving 3x = -9 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 3x + -12x = -9 + 12x + -12x Combine like terms: 3x + -12x = -9x -9x = -9 + 12x + -12x Combine like terms: 12x + -12x = 0 -9x = -9 + 0 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| -32-8x=-8(1+4x) | | 49v^2+42v+9=0 | | -49-3p=-4-12p | | 3x=12x-2 | | cos(x)-sin(x)=1 | | -10=p-12 | | 10=3u-11 | | -24-x=5x-9x-9 | | p+8=-2 | | 4p^2+9p-9=0 | | 9x-5x=-20 | | b+4=23 | | x-17=-28 | | -2=v-8 | | -12+x=-17 | | 7x+14y=122 | | -9=r-16 | | 6p^2-13p+7=0 | | -x^2-40x-76=0 | | 26=x+17 | | -2-5(1-4)=127 | | 14=-4+n | | 3(2+v)= | | 18=6-3-3 | | -4x-6=12y | | 4(x)+2(23-x)=62 | | k-20=-40 | | 4x-6=12y | | 9.8x+2.4y-8.1=0 | | -20+a=-2 | | -25=-16+N | | 4sin(0)= |